Mechanical and biological properties of Ti–(0–25 wt%)Nb alloys for biomedical implants application. Issue 1 (28th November 2019) - Zhang, Yuqing; Sun, Danni; Cheng, Jun; Tsoi, James Kit Hon; Chen, Jiang
Abstract: Binary titanium–niobium (Ti–Nb) alloys have recently been attracted due to low Young's moduli and non-toxic properties. This study explores the influence of low Nb content (0–25 wt%) on the comprehensive parameters of tensile stress–strain relationships (ultimate strength (σUTS ), yield strength (σ0.2 ) and elastic modulus ( E )), surfaces properties (Vickers microhardness, surface roughness ( R a ), water contact angle (WCA), X-ray diffraction (XRD) and scanning electron microscopy (SEM)), corrosion resistance (in artificial saliva and lactic acid) and biological properties (cytotoxicity and alkaline phosphatase activity of MC3T3-E1 pre-osteoblasts) of Ti– x Nb alloys ( x = 5, 10, 15, 20 and 25 wt%), with using commercially pure grade 2 titanium (cp-Ti) as control. XRD results shown that all the Ti– x Nb alloys comprised α + β Ti alloy phases, such that the β phase increased correspondingly with the increased amount of Nb in the alloy, as well as the reduction of E (69–87 GPa). Except Ti–5Nb, all other Ti– x Nb alloys showed a significantly higher hardness, increased σUTS and σ0.2, and decreased WCA compared with cp-Ti. No corrosion was detected on Ti– x Nb alloys and cp-Ti in artificial saliva and lactic acid solutions. The cytotoxicity of Ti– x Nb alloys was comparable to that of cp-Ti in MC3T3-E1 pre-osteoblasts without interference from differentiation behaviour, but the proliferation rate of the Ti–5Nb alloy was lower than other groups. In overall, binary Ti–(10–25 wt%)Nb alloys are promising candidate for orthopaedic and dental implants due to their improved mechanical properties and comparable biological performance, while Ti–5Nb should be used with caution.